(untitled) (ASEAN Engineering Journal, 2013)
Recent developments in nanotechnology have demonstrated that nano-bioceramics play an important role in the biomedical field due to their superior biological and mechanical properties compared to that of conventional bioceramics. However, a long sintering duration and high temperature used in conventional sintering have remained as a challenge to preserve the nano-structure of the sintered materials. Microwave synthesis, drying and sintering of phosphate-based bioceramics have emerged in recent years as new methods which offer significant benefits against conventional methods. As a prelude, a brief discussion on the fundamental aspects of microwave and microwave heating is also introduced. Subsequently, the applications of microwave in phosphate-based bioceramics are evaluated in detail.